Masalah Eksekutabilitas Putusan Mahkamah Konstitusi oleh Mahkamah Agung - Budi Suhariyanto (The Constitutional Court of the Republic of Indonesia, 2016)
Normatively constitutional court and supreme of court has on equal position with a different authority. However, there is a relationship of authority and point of contact. Morever, potential to cause disharmony on law enforcement. For example, on implementation of the constitutional court’s decision directly followed by the decision of the supreme court but some others not. The constitutional court’s decision characteristic are final and binding general (erga omnes), at the same level with legislation (negatif legislator), undirectly binding and enforced by the supreme court. Fundamentally, judge at the supreme court and the courts below is not a mouthpiece of the law, therefore it has some authority to interpre the statute (was also againts the decision of the constitutional court) to be applied on cases they handle. Although the judges decision of the supreme court do not decide on the validity and constitutionality of the norm, but through the efforts of the discovery or the interpretation of the law can gives an effect to the law enforcement and the establishment of a progressive and responsive legal reform.